JFQ volume 56 issue 7 Cover and Back matter (Journal of Financial and Quantitative Analysis, 2021)
Should companies be run for profit or purpose? This book shows how they can deliver both -based on rigorous evidence and an actionable framework. This edition, updated to include the pandemic and latest research, explains how managers, investors and citizens can put purpose into practice -and overcome the difficult trade-offs that hold them back.